Demorest's Family Magazine - Demorest, William Jennings (New York: W. J. Demorest, 1881)
Demorest's Family Magazine. March 1881. Vol. 17, no. 3. -- Victoria: A Woman's Statue -- The Unsung Song -- Seed-time and Harvest -- Archacon -- Stories from the Classics -- Gleanings from Ruskin -- An Extraordinary Case of Somnambulism -- Kith and Kin -- A Visit to the Galleries and Museums of the Hermitage at St. Petersburg -- Talks with Women: "George Eliot" -- One Foot in the Grave -- A Legend -- House and Home: My Housekeeping Class -- House Decorations -- Boys’ Rooms -- Women of Yesterday and To-day: Frau Ottilie Wildermuth -- Letters from Europe.—No. 1 -- Editorium: Methods of Charity -- " Keeping Accounts." -- Good Times -- " Uncle Toby and the Widow.” -- Cause of Depravity in the Young -- “The First Sunbeam.” -- Scandal from the Pulpit -- "How to Get into Good Society" -- Utilization of Waste Chambers -- Current Topics: Notes and Comments on Events of the Day -- Scientific Items -- Kitchen -- Young America: Prunes and Prisms -- What shall I be, Mother? -- Shoe-Bag -- Needle-book -- Sofa Afghan (Crochet) -- New Embroidery -- Crochet Edging -- Mirror of Fashions -- Review of Fashions -- Models for the Month -- Gloves -- Capuchin Ulster -- "What to Wear" -- Fashionable Jewelry -- Our Spring “ Portfolio” for the Spring and Summer of 1881 -- Stylish Short Costumes -- Theater Dress -- The Novelties in Dress -- Spring Brown and Spring Green -- Costume Hats and Bonnets -- Sleeves -- Newest Styles in Mourning -- Lenten Dresses -- Our "Illustrated Journal" -- Wedding Dresses -- Boy's Suit and Miss's Costume -- Children's Fashions -- Spring Materials, and Decorative Embroidery -- Description of Cut Paper Pattern -- Bonita Paletot -- Lancelot Suit -- Ladies' Club -- Diamonds of Thought -- Spice Box -- A Beautiful Panel Picture -- A Faithful Worker -- Success in Business: The Career of a New Jersey Organ Builder -- Our Parlor Pictures --
Mme Demorest's Mirror of Fashions
New York Illustrated News
Digitized from original print. Valdosta State University Archives and Special Collections. July 20, 2017. Original print has damage from p 137 - Mirror of Fashion p 50.
Keywords: Magazines; Catalogue; Women's History; Illustrated Periodicals; Periodicals; Dressmaking; Needlework; Homemaking; Fashion; Travel; 1800s; 19th Century; United States; Social History; Women; Children